2011
DOI: 10.1007/s10802-011-9598-z
|View full text |Cite
|
Sign up to set email alerts
|

The Relations among Maternal Depressive Disorder, Maternal Expressed Emotion, and Toddler Behavior Problems and Attachment

Abstract: Direct and indirect relations among maternal depression, maternal Expressed Emotion (EE: Self- and Child-Criticism), child internalizing and externalizing symptoms, and child attachment were examined. Participants were mothers with depression (n = 130) and comparison mothers (n = 68) and their toddlers (M age = 20 mo.; 53% male). Assessments included the Diagnostic Interview Schedule (maternal depression); the Five Minute Speech Sample (EE); the Child Behavior Checklist (toddler behavior problems); the Strange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 63 publications
6
51
1
4
Order By: Relevance
“…Transition from hospital to home is also a recognised time of additional stress for parents and higher levels of anxiety have also been previously reported in another study of parents with CHD at the time of hospital discharge [30]. Such disruptions to the parental role, and parental feelings of anxiety and depression, may potentially impact negatively on the attachment process which in turn may have implications for the infant's later development and therefore this is a vitally important issue to address [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Transition from hospital to home is also a recognised time of additional stress for parents and higher levels of anxiety have also been previously reported in another study of parents with CHD at the time of hospital discharge [30]. Such disruptions to the parental role, and parental feelings of anxiety and depression, may potentially impact negatively on the attachment process which in turn may have implications for the infant's later development and therefore this is a vitally important issue to address [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 84%
“…High levels of distress may disrupt normal interactions between the parent and infant, interfere with the parent-infant attachment process [3][4][5], and impact negatively upon the infant's intellectual and behavioural development, educational attainment, and mental health [6][7][8]. It is therefore feasible that parents of infants admitted to the Neonatal Intensive Care Unit (NICU) may be at risk of additional distress.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found, for example, that maternal depression negatively impacts maternal sensitivity, responsivity, and engagement with the infant, and mother-child interactions tend to be characterized by greater negativity, less facial empathy, and poor communication (Albright and TamisLeMonda 2002;Beebe et al 2012;Murray 1992;O'Hara 2009). Infants also learn how to regulate their emotions from the affective messages they receive from their mothers, and it has been suggested that the relay of negative feelings through facial expressions and verbal and non-verbal behaviors may impede healthy emotional development (Albright and TamisLeMonda 2002;Gravener et al 2012). In fact, research shows that infants and toddlers of depressed mothers display more negative and less positive affect themselves (Albright and Tamis-LeMonda 2002;Feldman et al 2009;Hart et al 1998;Righetti-Veltema et al 2002).…”
Section: The Effects Of Maternal Depression On Infant and Toddler Devmentioning
confidence: 99%
“…Another limitation is the assessment of psychiatric symptoms in the adolescents only. Given that maternal psychopathology has been found to relate to more critical EE (Gravener et al, 2012), it is likely that the presence of maternal psychopathology would predict more criticism. Thus, caregiver psychiatric symptoms may moderate the relation between adolescent BPD symptoms and perceived caregiver criticism.…”
Section: Discussionmentioning
confidence: 99%